2018
DOI: 10.1002/ecy.2198
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and an invasive, tropical milkweed: an ecological trap for monarch butterflies

Abstract: While it is well established that climate change affects species distributions and abundances, the impacts of climate change on species interactions has not been extensively studied. This is particularly important for specialists whose interactions are tightly linked, such as between the monarch butterfly (Danaus plexippus) and the plant genus Asclepias, on which it depends. We used open-top chambers (OTCs) to increase temperatures in experimental plots and placed either nonnative Asclepias curassavica or nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…Although such traps are predicted to occur frequently because of the prevalence of invasive plants (Davis & Cipollini, 2014;Faldyn et al, 2018), few attempts have been made to identify characteristics of invasive plants that might increase the likelihood of the formation of an ecological trap. In this study, we found that the invasive plant Spartina can be an ecological trap for the native insect Laelia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although such traps are predicted to occur frequently because of the prevalence of invasive plants (Davis & Cipollini, 2014;Faldyn et al, 2018), few attempts have been made to identify characteristics of invasive plants that might increase the likelihood of the formation of an ecological trap. In this study, we found that the invasive plant Spartina can be an ecological trap for the native insect Laelia.…”
Section: Discussionmentioning
confidence: 99%
“…Plant invasions pose a major threat to ecosystem structure and functioning world-wide (Mack et al, 2000;Vilà et al, 2011). Exotic plant invaders can transform resident herbivore assemblages by modifying their habitats (Wu et al, 2009), food resources (Faldyn, Hunter, & Elderd, 2018) and interactions with native species (Bezemer, Harvey, & Cronin, 2014;Shapiro, 2002), which may positively or negatively impact herbivore populations and modify community structure (reviewed by Bezemer et al, 2014). Novel interactions between invasive plants and native herbivores have three possible outcomes: (a) herbivores adopt novel plants as hosts and benefit from additional host availability; (b) native herbivores fail to exploit invasive plants as new hosts or only rarely consume them and receive no fitness costs or benefits; and (c) 'mismatches' occur when native herbivores recognize invasive plants as hosts but suffer reduced fitness such as poor development of juveniles (Davis & Cipollini, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species caught in an evolutionary trap in at least a portion of their range include charismatic megafauna (African wild dogs, Lycaon pictus : van der Meer, Fritz, Blinston, & Rasmussen, ; Rasmussen, Gusset, Courchamp, & Macdonald, , leopards, Panthera pardus : Balme, Slotow, & Hunter, ; Burton, Sam, Balangtaa, & Brashares, , hawksbill sea turtles, Eretmochelys imbricata : Leighton, Horrocks, Krueger, Beggs, & Kramer, ), and microfauna [monarch butterfly], Danaus plexippus : Faldyn, Hunter, & Elderd, ), animals of economic importance that humans rely upon for food (tuna, Scombridae spp. : Hallier & Gaertner, ; Jaquemet, Potier, & Ménard, , coho salmon, Oncorhynchus kisutch : Jeffres & Moyle, ), as well as the most important pollinators of human food crops (European honey bees, Apis mellifera : Kessler et al, ; Rundlöf et al, , Table ).…”
Section: Evolutionary Traps As a Conservation Threatmentioning
confidence: 99%
“…This paucity of studies may be attributed to the fact that biotic interactions are often difficult to quantify (McCain & Grytnes, 2010) and that cause and effect can be difficult to distinguish in the relationship between biotic interactions and species diversity (Fischer, 1960; Schemske et al, 2009). However, there is a growing need to study the role of these interactions in shaping diversity patterns in the light of predicted shifts in species ranges due to climate change (Anderson, 2017; Blois, Zarnetske, Fitzpatrick, & Finnegan, 2013; Gavish et al, 2017; Valiente‐Banuet et al, 2015; Wisz et al, 2013), especially as the strength and effects of these interactions are themselves susceptible to climate change (Faldyn, Hunter, & Elderd, 2018; Tylianakis, Didham, Bascompte, & Wardle, 2008).…”
Section: Introductionmentioning
confidence: 99%